An analytical study of the fragmentation of agricultural holdings in Lattakia Governorate - شعباني, باسل; غسان يعقوب ,; إبراهيم صقر, (Latakia University Journal -Biological Sciences Series, 2023)
The study was conducted in Lattakia Governorate on a random sample of 384 holders in 24 villages, through which the phenomenon of fragmentation of agricultural holdings was identified. The study aimed to achieve the following: Studying the reality of the phenomenon of fragmentation and dispersal of agricultural holdings and determining its causes in Lattakia Governorate. A study of fragmentation, holding capacity, and fair distribution of agricultural holdings in Lattakia Governorate. The study showed the degree of fragmentation of holdings in the coastal plains, which ranged between 0.0361 and 0.0914, and between 0.0063 - 0.1441 in the mountainous highlands, and between 0.0054 and 0.0559 at the level of the total sample. The value of the Gini coefficient was about 0.45 in the coastal plains, 0.40 in the mountainous highlands, and 0.49 at the level of the total sample. Which indicates inequality in the distribution of holdings. The study concluded that activating the role of cooperatives is one of the effective solutions to the problem of fragmentation, in addition to limiting the construction of touristic and industrial housing projects and transportation methods in agricultural areas, supporting the countryside with what it needs for agricultural and rural development to meet the challenges of low living resources that cause the migration of rural people to their areas towards livelihood The city, as well as the migration of rural people to their lands and the search for other sources to meet their needs.